EVERYTHING’S GONE GREEN: THE ENVIRONMENT OF BP’S NARRATIVE - Hitchcock, Peter (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
This essay looks at a particularly galling phenomenon for environmentalism, the “green” globalism of an oil conglomerate. Rather than simply dismiss such gestures as corporate cynicism, the paper suggests that one might usefully pay attention to the narrative modes at stake in these initiatives which here connect the exploitation of modernity to a parabolic logic. BP’s going green is seen as an extension rather than as a contravention of its social being and shows why, even after the Deepwater Horizon disaster, BP’s desire to move “beyond petroleum” means more rather than less oil exploitation.